Association between High-Sensitivity C-Reactive Protein and N-Terminal Pro-B-Type Natriuretic Peptide in Patients with Hepatitis C Virus Infection - Wenliang Che; Buchun Zhang; Wenling Liu; Yidong Wei; Yawei Xu; Dayi Hu (Mediators of Inflammation)
Background. Prior study showed HCV-infected patients have increased serum N-Terminal Pro-B-Type Natriuretic Peptide (NT-proBNP) and a possible left ventricular diastolic dysfunction. The objectives of the present paper were to investigate the characteristics of hs-CRP and its correlation with clinical profiles including NT-proBNP and echocardiographic variables in HCV-infected patients. Methods and Results. A total of 106 HCV-infected patients and 106 control healthy individuals were enrolled. The level of serum hs-CRP (median 1.023 mg/L, range 0.03∼5.379 mg/L) was significantly lower in all 106 patients than that in controls (median 3.147 mg/L, range 0.08~7.36 mg/L, P=0.012). Although hs-CRP did not correlate significantly with NT-proBNP when all patients and controls were included (r=0.169, P=0.121), simple regression analysis demonstrated a statistically significant linear correlation between hs-CRP and NT-proBNP in HCV-infected patients group (r=0.392, P=0.017). Independent correlates of hs-CRP levels (R2=0.13) were older age (β′=0.031, P=0.025) and NT proBNP (β′=0.024, P=0.017). Conclusions. Although the level of serum hs-CRP decreased significantly, there was a significant association between hs-CRP and NT-proBNP in HCV-infected patients.